Novel naphthalene-tetrazole butanamide derivatives: synthesis and evaluation of acetylcholinesterase inhibitory activity - Nguyen Viet Hung; Nguyen Anh Chi, Hoang Tran, Tiep K. Nguyen; Van-Hai Hoang; Tran Thi Thu Hien; Le Minh Dong; Phuong-Thao Tran (Vietnam Journal of Science, Technology and Engineering, 2026)
Acetylcholinesterase (AChE) inhibitors constitute a well-established class of therapeutic agents that provide symptomatic relief in Alzheimer’s disease, underscoring the continued importance of developing new compounds with improved efficacy and safety profiles. In this context, five novel derivatives bearing the 4-(5-(naphthalene-2-yl)-2H-tetrazol-2-yl)-N-phenylbutanamide scaffold were synthesised through four known reactions: [3+2] cycloaddition, N-alkylation, saponification, and amidation. The purity of the compounds was confirmed by melting point analysis and thin-layer chromatography (TLC). Structural characterisation was achieved using infrared spectroscopy (IR), high-resolution mass spectrometry (HRMS), and proton and carbon nuclear magnetic resonance spectroscopy (1H-NMR and 13C-NMR). The acetylcholinesterase inhibitory activity of the synthesised compounds was evaluated at five concentrations to determine their IC50 values. Compound IVa exhibited the highest inhibitory potency, with an IC50 of 467.82±10.77 μM. In addition, the inhibitory potential of the compounds was analysed in relation to their physicochemical properties, including drug-likeness and blood-brain barrier permeability, with none violating Lipinski’s rule. Molecular docking studies further revealed that the naphthalene-containing framework demonstrated strong predicted binding affinity to AChE, which may contribute to the observed inhibitory activity. These findings provide novel and valuable structural insights for the development of AChE inhibitor derivatives as potential therapeutic strategies for Alzheimer’s disease.